Analisis Tingkat Kesejahteraan Nelayan Di Desa Paluh Sibaji Dengan Metode CIBEST - Chuzaimah Batu Bara, Reni Armayani Hasibuan, Nurhalisa (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2022)
The thesis entitled "Analysis of the Welfare Level of Fishermen in Paluh Sibaji Village with the CIBEST Method" by Nurhalisa under the guidance of Advisor I Dr. Chuzaimah Batubara, MA and Advisor II Reni Ria Armayani Hasibuan, MEI. Welfare in Islam is..the..condition..of..a person..who..is materially and spiritually prosperous. Paluh Sibaji village is a coastal area in Deli Serdang Regency where fishermen are synonymous with..poor people and live in slums but this is not the case with fishermen in this village. This..study aims to determine the welfare level of fishermen in Paluh Sibaji Village using the CIBEST method. The method used is qualitative. The data analysis technique uses..income analysis and CIBEST analysis which uses the SPSS Version 22 application to process the data. The results..showed..that..the welfare of fishermen in Paluh Sibaji village using the CIBEST method from 89 samples taken to observe that the majority of fishermen in Paluh Sibaji village are in..Quadrant I (Sejahtera) which means that fishermen are materially and spiritually prosperous as many as 46 fishing households. Quadrant II (Material poverty) as many as 4 households. Quadrant III (spiritual poverty) is 35 households and Quadrant IV (absolute poverty) is 4 households. And the net income of fishermen in Paluh Sibaji Village in one month, the majority of them have a nominal income of Rp. 3,000,000-Rp. 6,000,000 which means that..the income of fishermen in Paluh Sibaji Village has exceeded the per capita income in Deli Serdang Regency, it can be concluded that the fishermen in Paluh Sibaji Village are mostly in a state of material prosperity and spiritually prosperous